PENGARUH RASIO KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA - Visakha, Olivia; Djashan, Indra Arifin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research is conducted to obtain empirical evidence regarding the factors influencing firm value in the manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2021 to 2023. The independent variables examined in this study include liquidity, activity, leverage, profitability, firm size, dividend policy, investment decisions, and firm growth. This study employs purposive sampling as the sampling method, which requires certain criteria until a usable sample size is obtained. Based on the sampling selection process, this research uses 44 companies with 132 data that successfully passed the selection criteria. The hypothesis testing conducted in this study utilizes multiple regression analysis. Based on the analysis results, this study concludes that liquidity, activity, leverage, and profitability have a positive effect on firm value. High profitability will increase the firm value because investors believe that the company is able to utilize its assets effectively to increase profits, which ultimately boosts investor confidence and raises the company's stock price. Meanwhile, firm growth has a negative effect on firm value. Additionally, firm size, dividend policy, and investment decisions do not affect firm value.